Mojo mayhem - Mooney, E. S.; McCracken, Craig; Goldberg, Barry (New York : Scholastic, 2002)
"Mojo's at it again...and this time he's not alone!"
"Based on 'The powerpuff Girls' as created by Craig McCracken."
"Cartoon Network"--T.p.
RL3.
006-009.
Keywords: Girls -- Juvenile fiction